Building Brand Equity through Viral TikTok Content Strategies: A Phenomenological Study of MSME Entrepreneurs - Farhat Abas; Annisa Hardini; Mira Mira; Nurul Faisah A.S; Tuti Herawati; Aep Saefullah (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
The rapid development of social media has fundamentally transformed digital marketing practices, particularly for Micro, Small, and Medium Enterprises (MSMEs). Among various platforms, TikTok has emerged as a prominent medium due to its strong viral potential, short-form video format, algorithm-driven content distribution, and dynamic trend culture. These characteristics position TikTok as a strategic tool for MSMEs in building and strengthening brand equity. This study aims to explore how MSME entrepreneurs interpret and implement viral TikTok content strategies in their efforts to develop brand equity. Employing a qualitative approach with a phenomenological method, this research investigates the subjective experiences of MSME actors who actively utilize TikTok as a marketing platform. Data were collected through in-depth interviews and systematic observations of TikTok content produced by MSMEs. The findings reveal that viral TikTok content strategies play a significant role in enhancing brand awareness, shaping positive brand associations, strengthening perceived quality, and fostering consumer brand loyalty. Content that is authentic, aligned with current trends, and delivered consistently is perceived as effective in creating emotional connections between brands and audiences. These results suggest that TikTok functions not only as a promotional channel but also as a strategic medium for constructing brand value among MSMEs. This study contributes to both theoretical discussions on brand equity and practical insights for MSME digital marketing strategies